A structured review of quality of life in advanced and high‐risk cutaneous squamous cell carcinoma shows the need for more studies and better measures. Issue 3 (7th May 2021) - Starkings, R.; Shilling, V.; Jenkins, V.; Fallowfield, L.
Abstract: Background: Cutaneous squamous cell carcinoma (cSCC) accounts for nearly a quarter of non‐melanoma skin cancers. Studies reporting Quality of Life (QoL) in this group focus on early stage disease. A small proportion of cSCC patients have high‐risk or advanced disease, with potentially significant QoL impacts, yet are largely overlooked. Aims: This structured review appraises measures and published QoL outcomes in this group. Materials & Methods: We conducted searches in MEDLINE, EMBASE, CINAHLplus and PsycInfo in June 2020 (updated in October) to identify publications specifically reporting QoL outcomes in this cohort. Returns were reviewed against a strict set of eligibility criteria. Results: We identified seven publications for inclusion; three relating to high‐risk cSCC, three to metastatic disease and one to unresectable disease. Publications were appraised for quality using the Mixed Methods Appraisal Tool. Only one fulfilled more than two of the five quality criteria. Studies employed a range of patient reported outcome measures to assess QoL, both generic and disease specific. Discussion: All studies with multiple time‐points reported stable or improving QoL, however extrapolation of these findings to the cSCC population is not warranted due to study limitations including mixed populations, incomplete data sets or single measurements. We set out to review the QoL literature for high‐risk and advanced cSCC and found a small and disparate body of evidence. Studies varied significantly in terms of study population, design and quality. While the identified studies suggested stable or improving QoL, we question the choice of measures used and highlight the need for further work in this area. Conclusion: While there are some published reports about quality of life for patients with early stage cutaneous squamous cell carcinoma, these impacts for the high‐risk or advanced cohort are largely unexplored. We conducted a structured review of published measures and outcomes used in this cohort and found a demonstrable need for further, targeted, exploration of patient needs in this area. Abstract : While there are some published reports about quality of life (QoL) for patients with early stage cutaneous squamous cell carcinoma (cSCC), these impacts for the high‐risk or advanced cohort are largely unexplored. We conducted a structured review of published measures and outcomes used in this cohort and found a demonstrable need for further, targeted, exploration of patient needs in this area.